SEJATI: Aplikasi Self-care berbasis Kecerdasan Buatan sebagai Upaya Menurunkan Risiko Depresi bagi Remaja - Xavier Herda Putri, Nidya Almira; Chusniyatuzzamrodah, Elva; Fauzan Prawira Arya , Muhammad; Indrijati, Herdina (Universitas Airlangga, 2022)
This research aims to measure the effectiveness of using SEJATI prototype as a digital application to reduce risk factors for depression in adolescents. SEJATI is an artificial intelligence-based application which focused on self-care that adolescents can do themselves with the support of artificial intelligence system to assess, determine the activities, and evaluate the success of the self-care activities as an alternative strategy that is less stigma and is able to overcome the limited access of mental health care services. SEJATI is developed by using research and development methods, which includes: planning, production, and evaluation. SEJATI prototype application is evaluated by 7 participants aged 15-24 years old using 1-5 range Likert scales. As the result, SEJATI reaches 88% as its Likert scale total percentage, which is also categorized as